Impact analysis of forest and peatland landscape change: Socio-economic and environmental implications - Biru, Muhammad Dilheim (Jurnal Bisnis Kehutanan dan Lingkungan, 2025)
Background:  Peat forest land is highly susceptible to burning and releasing stored carbon and greenhouse gas emissions into the earth's atmosphere when its water content is used for plantations, agriculture and other uses. This study was conducted to analyze the progress of forest and peatland landscape development in Katingan District, Central Kalimantan Province and its potential ecological impacts on the environment. Methods: This research approach uses a quantitative approach to analyze landscape changes that occur within five years, namely in 2015 and 2020. The research was conducted by examining secondary data only. Finding:  The results of this study show that the contrast in land increase between forest and peat land and non-forest land is not significant, as shown by the ratio of forest and peat land/non-forest land which increased by only 0.02 or 2% between 2015 and 2020. If the area of non-forest land continues to increase in the future, Katingan Regency is predicted to have a higher vulnerability to natural disasters. Conclusion: The results of land cover/landscape change in Katingan District, both forest and peatland (consisting of primary dry forest, secondary dry forest, secondary mangrove, swamp, swamp scrub, and secondary swamp forest) and non-forest land, both increased in area, respectively by 26,532.61 ha and 4813.64 ha from 2015 to 2020. Novelty of This Study: This study provides a unique perspective on the ecological impact of land cover changes in Katingan District by analyzing a five-year landscape transformation using a quantitative approach.